The Relationship between Spirituality and Self-management of Chronic Illness among Old Age at Geriatric Care Homes in Baghdad - Faraj, Raad K. (International Journal of Psychosocial Rehabilitation, 2020)
Objectives: The study aims to evaluate the level of spirituality and self-management of chronic illness among old age clients and find out the relationship between the spirituality and self-management. Methodology: A descriptive correlational design that is initiated for the period of June 1st to December 1st, 2019; the study includes two geriatric Homes at Baghdad city. The sample of the study includes (100) old age residents at geriatric homes that are selected by use of the convenient sampling method (non-probability sample). The questionnaire of the study is arranged; for measuring the spirituality, the Spiritual Well-Being Scale is used; and for measuring the self-management, the Self-Efficacy for Managing Chronic Disease 6-item Scale is used. The data have been collected through the utilization of the self-administrative report and structured interview. Statistical analyses were conducted by using statistical package for social science (IBM SPSS Statistics) version 24.0. Results: The study found that old age residents are with age group (60-69) year old (47%). who are male (55%), divorced (39%), read and write (33%), and with personal source of income (45%). The common chronic illness among elderly are: hypertension (35%), diabetes mellitus (18%), and arthritis (15%). (65%) of them are showing moderate level of spiritual well-being and (55%) showing high level of self-efficacy for managing chronic illness. There is high significant correlation between spiritual well-being and self-efficacy among elderly. Conclusions: The study concluded that spirituality has high positive role in self-management abilities for managing the chronic illness among elderly. Recommendations: The study recommended increasing the spiritual well-being among the elderly to improve the quality of their life that have the role in improving the self-management abilities for chronic illness.